(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Assessing the value of ultrasound in diagnosing biliary atresia at the National Hospital of Pediatric from 2021 to 2023 Methods: A cross-sectional study was carried out on 72 patients with cholestasis and had the final diagnosis of biliary atresia or not due to exploratory surgery associated with cholangiogram and had pathology results. All patients had been performing conventional and Doppler ultrasonography, Elastography due to BA protocol pre-operation. Results: The irregular gallbladder wall’ sign has Se 81.2%, Sn 93.3%, PPV 96.3%,; gallbladder’s length </= 15mm has Se Se 63.6%, Sn 94.1%. In the group of gallbladder’s length longer than 15mm, the value of irregular gallbladder’s wall is Se 70%, Sn 100%, PPV 100%Triangular cord sign (TC sign) has the area under ROC curve 0.87, liver elasto value 0.85. Hepatic sub capsular flow (HSF) has Se 96.4%, Sn 64.7%, Multivariate analysis in the entire group when combinating the characteristics of gallbladder size and irregular wall: if having at least one sign positive will has Se 87.2%, Sn 94.1%. In the group having gallbladder, when combinating 3 characteristics of the gall blader length, irregular wall, and contraction, the highest values if having at least 2 signs with Se 80.9%, Sn 94.1%. In the negative 2D ultrasound group, the values of HSF are 75%, 80%. Conclusion: Ultrasound, including both conventional and advanced techniques, has high diagnostic value in the assessment of biliary atresia